SlNRT1.5 transporter and the SlSKOR K+ channel jointly contribute to K+ translocation in tomato plants - Martínez-Martínez, Almudena; Botella, María Ángeles; García-Legaz, Manuel Francisco; López-Gómez, Elvira; Amo, Jesús; Rubio-Valverde, Lourdes; Fernández-García, José Antonio; Martínez, Vicente; Rubio, Francisco; Nieves-Cordones, Manuel (Elsevier, 2024)
Accumulation of K+ in shoots is largely dependent on K+ transport via the xylem and has important implications not only for K+ nutrition but also for stress tolerance. In tomato plants, the K+ channel SlSKOR contributed to K+ translocation but the decrease in the shoot K+ content in slskor mutants was only ~15 %, indicating that additional K+ transport systems operated in the tomato stele. Here, we studied the physiological roles of the transporter SlNRT1.5 in tomato plants, whose homolog in Arabidopsis, AtNRT1.5, contributed to xylem K+ load. By using heterologous expression of SlNRT1.5 in Xenopus oocytes and a slnrt1.5 knock-out mutant, we have gained insights into its role in shoot K+ nutrition. Expression of SlNRT1.5 in Xenopus oocytes resulted in K+ efflux, similar to that mediated by AtNRT1.5, which could indicate that SlNRT1.5 operates as a K+ transport system. Plants lacking slnrt1.5 accumulated less K+ in shoots than WT plants under low external pH (4.5), and low supply of K+ (0.05 mM) and N (0.5 mM). Interestingly, slnrt1.5 plants accumulated less Na+ and Cl- in shoots than WT plants. Further analyses on slskor slnrt1.5 double mutant plants revealed an overlapping role of SlSKOR and SlNRT1.5 in shoot K+ accumulation. Double mutants showed a 40 % decrease in shoot K+ content in comparison with slskor and slnrt1.5 single mutants. Altogether, this study showed that SlNRT1.5 and SlSKOR are major players in shoot K+ accumulation in tomato plants.
Keywords: Tomates; Plantas; Potassium; Tomato NRT transporter; Translocation; Nutrient deficiency; CRISPR-Cas